CONTENTS AND FEATURES OF THE USE OF THE ELECTRONIC MANUAL "BIOLOGICAL PHYSICS" IN MEDICAL INSTITUTIONS OF HIGHER EDUCATION - Makarenko, Oleksandr; Makarenko, Kateryna; Makarenko, Volodymyr; Silkova, Olena; Matiash, Liudmyla (Physical and Mathematical Education, 2023)
Formulation of the problem. An actual problem for a modern higher school is the development and use in the educational process of digital tools that can be used to provide classroom, independent, and distance learning. The purpose of the study is to reveal the content and conditions of operation of the electronic textbook "Biological Physics" during the study of medical and biological physics by future doctors in medical universities.Materials and methods. To find out the state of development of the research problem in pedagogical theory and practice, the following theoretical analysis, comparison, generalization, and systematization were used. To achieve the goal, the following were used: a questionnaire of future doctors to determine the type of information perception; pedagogical observation of their work with the electronic manual; expert evaluation to identify forms that activate the functioning of the electronic manual. The results of the questionnaire were processed using statistical methods.The results. The authors analyzed the content and conditions of operation of the electronic textbook "Biological Physics". In the structure of each of its topics, theoretical and practical parts and means for self-control are highlighted. This structure is considered in the example of studying one of the topics. The implementation of transitions to various types of activities is shown. The competency-based approach to education is revealed. The conditions for the functioning of the electronic manual in the training of future doctors are highlighted, including taking into account the types of perception of information by future doctors; creation of a specific educational environment centered on the computer; a harmonious combination of the electronic manual with other teaching aids; taking into account its features when choosing forms and methods of education; taking into account the specifics of distance learning when using it.Conclusions. Analysis of the experience of scientists, methodologists, and own research of the selected operating conditions of the electronic textbook "Biological Physics", we can conclude that its use activates the work of students. A series of electronic manuals using tasks and exercises of medical and biological content requires further research.
Keywords: electronic manual; future doctors; medical and biological physics; individual work; Lab